2020
DOI: 10.18471/rbe.v33.33828
|View full text |Cite
|
Sign up to set email alerts
|

Prática Clínica Da Equipe De Enfermagem Acerca Da Terapia Intravenosa Em Unidade Neonatal E Pediátrica

Abstract: <p><strong>Objetivo:</strong> analisar a prática assistencial de uma equipe de enfermagem acerca da terapia intravenosa no setor de neonatologia e pediatria. <strong>Método:</strong> estudo de abordagem quantitativa, descritivo e exploratório em um hospital público no interior do Rio de Janeiro, Brasil. A técnica de coleta de dados foi a entrevista desenvolvida entre setembro e novembro de 2017. <strong>Resultados:</strong> amostra composta por 9 (31,1%) enfermeiros e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…19,21 When the child has the opportunity to play and dramatize IVT, through ITP, the pain, loneliness, fear and crying are alleviated. Corroborating the results of contemporary studies on the use of ITP to prepare hospitalized children for IVT, 5,21,23,25,26 it was possible to glimpse the expression of positive responses of the child after this technique, of which we can mention: the reduction of fear; tranquility before the procedure; the relaxed posture; the cooperation of the child; the greater interaction with the health team and other children hospitalized and the reduction of tension levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…19,21 When the child has the opportunity to play and dramatize IVT, through ITP, the pain, loneliness, fear and crying are alleviated. Corroborating the results of contemporary studies on the use of ITP to prepare hospitalized children for IVT, 5,21,23,25,26 it was possible to glimpse the expression of positive responses of the child after this technique, of which we can mention: the reduction of fear; tranquility before the procedure; the relaxed posture; the cooperation of the child; the greater interaction with the health team and other children hospitalized and the reduction of tension levels.…”
Section: Discussionmentioning
confidence: 91%
“…However, the use of IVT in pediatric care is characterized as a stressful event, capable of triggering, in the hospitalized child, alert senses, distrust, stress, fear, anxiety and physical pain. [3][4][5] Despite the care during the child's hospitalization, it is up to the nurse professional to identify the signs of physical and emotional changes them, due to the IVT actions, and manage them. In this sense, play appears as an increased tool to change the inert routine of hospitalization, since it is able to reduce trauma in children, positively influence their physical and emotional recovery, and encourage them to face atypical situations.…”
Section: Introductionmentioning
confidence: 99%
“…In a descriptive study conducted with nurses and nurse technicians who worked in neonatal and pediatric, it was asked which VAD was selected for the patient and the results showed that, regardless of the age group and duration of the IV therapy, the CIP was the only device used. 27 The use of miniMAGIC-Brasil can provide additional information to clinicians and can potentially result in a more varied and appropriate approach to vascular access in children and newborns, thereby reducing infections and thromboses.…”
Section: Discussionmentioning
confidence: 99%
“…In this therapy, pain comes from the insertion of peripheral catheters in one of the blood vessels, in addition to the fixation, maintenance, drug administration and removal when their use is no longer indicated, or due to expiration date according to the institution's criteria and, also, due to accidental loss of the access (4) . Although IVT is a crucial element in the arsenal of care measures for hospitalized children, its use generally culminates in a stressful, difficult and painful event, translated by this population into a feeling that refers to a constant state of alert, added to distrust, stress, fear, anxiety and physical pain (5) . As a technological resource to help reduce discomfort and tensions, there is the possibility of using Virtual Reality (VR).…”
Section: Introductionmentioning
confidence: 99%